Last-Mile Delivery Alternatives’ Effect on Consumer Behavior - El-Segaier, Osama; Milenkovic, Emilio (My University, 2023)
E-commerce has seen a steady increase in consumption over previous years, where PostNord documented a 40% increase in 2020 followed by a 20% increase in 2021. This can be due to various factors, such as the technical advancements of transportation technology, however in these specific years the main reason for the increase in consumption likely falls on the Covid-19 pandemic. Various studies conducted on the consumer behavior of e-commerce consumers have identified delivery as a key component to the level of consumption by consumers. This paper aims to study and analyze the effect that different levels of delivery alternatives have on a consumer based on personal factors. Through surveying 211 consumers of different gender, age, educational level and frequency of purchase, this study finds that the cost of delivery is considered as the most important attribute, followed by speed. This result is in agreement with previous conducted in this matter. The study does not, however, consider other factors that may affect the consumer’s behavior, such as price of the product, type of product and the presence of competitors.
Keywords: Logistics; e-commerce; retail; consumer behavior; online